The genus Lepidaploa (Vernonieae, Asteraceae) in southern South America - Marques, Danilo; Farco, Gabriela Elizabeth; Nakajima, Jimi Naoki; Dematteis, Massimiliano (Phytotaxa, 2018)
A morphological analysis of the genus Lepidaploa (Vernonieae) of southern South America has been carried out. Until now, the information concerning the genus was fragmented and incomplete for this region. Altogether, 13 species are described and illustrated here. A comprehensive key to the species of southern South America is presented; in addition, we characterized and delimited the distributions of the species.